New essays in technical and scientific communication : research, theory, practice - Anderson, Paul V.; Brockmann, R. John; Miller, Carolyn R. (Baywood's technical communications series, 1983)
Represents an important collection of writings about technical communications. Focusing on a range of theoretical and practical issues, this title includes essays which reflect the rigor, vitality, and interdisciplinary nature of modern technical communications.